2014
DOI: 10.1186/1748-717x-9-92
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the dose-volume relationship on and risk factors for maxillary osteoradionecrosis after carbon ion radiotherapy

Abstract: BackgroundOsteoradionecrosis (ORN) is a critical complication after carbon ion (C-ion) or photon radiotherapy (RT) for head and neck tumors. However, the risk factors for ORN after C-ion RT remain unclear. Therefore, the present study aimed to investigate the effects of the dose-volume relationship on and risk factors for ORN development after C-ion RT. We, however, focused on the maxillary bone because most tumors treated with C-ion RT were primarily located in the sinonasal cavity.MethodsThe patients enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 14 publications
4
66
1
Order By: Relevance
“…Kuhnt et al reported that 6.6% of 775 patients with head and neck cancer developed severe ORN that required extensive surgical intervention after photon RT, with the highest frequency being observed for oral cavity tumors (13.6%) . Similarly, the present study revealed an incidence of 13.5% for grade 3 ORN among patients with oral malignancy who underwent C‐ion RT, which is higher than the incidence from our previous study of head and neck malignancies (4.8%) . Thus, it appears that C‐ion RT and photon RT were associated with similar incidences of grade 3 ORN, despite the fact that the areas of ORN were localized because of the dose‐localization properties of carbon ions …”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Kuhnt et al reported that 6.6% of 775 patients with head and neck cancer developed severe ORN that required extensive surgical intervention after photon RT, with the highest frequency being observed for oral cavity tumors (13.6%) . Similarly, the present study revealed an incidence of 13.5% for grade 3 ORN among patients with oral malignancy who underwent C‐ion RT, which is higher than the incidence from our previous study of head and neck malignancies (4.8%) . Thus, it appears that C‐ion RT and photon RT were associated with similar incidences of grade 3 ORN, despite the fact that the areas of ORN were localized because of the dose‐localization properties of carbon ions …”
Section: Discussionsupporting
confidence: 62%
“…Thus, it appears that reconstruction using only soft tissue flaps after sequestrectomy may be acceptable for patients who are treated using C‐ion RT. In addition, we have reported that the presence of teeth within the PTV and the volume of the maxillary bone receiving ≥50 Gy (RBE) are independent risk factors for ORN after C‐ion RT . Therefore, to reduce the risk of ORN, we routinely perform preemptive extraction of teeth with poor prognoses that are near the irradiation field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, 2 patients developed grade 3 mandible osteoradionecrosis. We recently reported the risk factors for developing maxillary osteoradionecrosis after C‐ion RT . In the multivariate analysis, a maxillary volume receiving >50 Gy (RBE) and the presence of teeth in the PTV were extracted as independent risk factors.…”
Section: Discussionmentioning
confidence: 99%